Hubungan Antara Stress Kerja Dan Motivasi Kerja Dengan Kinerja Karyawan - Damayanthi, Emiliana Luh (Persona:Jurnal Psikologi Indonesia, 2015)
The purpose of the research is to know the correlation between the job stress and work motivation with employee performance. The subject for this research who are 50 non nursing participants. This result shows there were significant correlation between job stress and work motivation with employee performance (F = 3.023, p<0.05), partially found result positive correlation significantly between the job stress with performance (t = 2.254, p = 0.029) and unsignificant correlation between work motivation with performance (t = 1.1341, p = 0.186).